Принципиальная схема реакторной установки для пиролиза твердых бытовых отходов в подвижном слое и экспериментально установленные особенности процесса - Шапорев, Валерий Павлович; Себко, Вадим Вадимович; Михайлюк, В. М. (НТУ "ХПИ", 2011)
Theoretical and experimental research of high-temperature pyrolysis process has been carried out as a result of allometric heating of municipal solid waste using hot gases generated in the reactor. Basic destruction mechanism of municipal solid waste’s organic composition has been derived. Fundamental reaction scheme for municipal solid waste pyrolysis has been developed.
Keywords: твердые бытовые отходы; переработка отходов; газификация; пиролиз; шахтный реактор; термическая деструкция; температурный режим; корреляция